A política nacional de desenvolvimento de pessoas e a prática dos incentivos à qualificação para servidores técnico-administrativos: uma avaliação a partir da experiência de uma instituição de ensino superior - Teixeira, Ciro Régis Lima (2022)
This work evaluates the National Policy for Personnel Development (PNDP) regarding the practice of incentives for qualification for technical-administrative servants, focusing on a higher education institution. This Policy is very important, given the number of employees of the Federal Executive Branch and the relevant services provided, which, inserted in a context of Managerial Public Administration, make the evaluation of its results very relevant, especially with regard to the qualification of servers as formal education. The study was applied taking into account Lejano's (2012) experiential model and sought to evaluate various actors impacted by the PNDP, with their different views, in addition to a documentary research on the implementation of the policy in the Institution, making it exploratory-descriptive. Thus, in this research, interviews were carried out with policy managers, questionnaires were applied to 342 employees who are direct beneficiaries of the policy and 6 managers were interviewed, in order to identify improvements in the performance of their teams, with the consequent improvement in the provision of public services. . It was unanimously concluded by the latter group that the qualification of their teams improves their performance, a vision shared also by the servers themselves and also by the policy managers. It is worth mentioning, in unison, the difficulty of access to qualification programs, either by the number of vacancies offered to civil servants, or by the difficulty of removal for qualification, among other aspects that were dealt with in more detail at work. It was also evaluated that the Policy is being implemented satisfactorily in relation to most of its guidelines, but that it still needs to improve in some aspects, especially in institutional support and in guaranteeing access, by the institution, of its staff. to qualifying actions.